2021
DOI: 10.1007/s00203-021-02580-4
|View full text |Cite
|
Sign up to set email alerts
|

The value of bacterial metagenomic analysis in post-surgical examination of gallstones

Abstract: Gallstone disease is one of the most common causes of hospitalization for gastrointestinal diseases in the world. Recent studies have examined the presence of bacteria in the formation of stones. Our main goal was to determine the overall composition of gallstone microflora. Gallstones were obtained from 24 patients during laparoscopic cholecystectomy from which DNA were extracted. Composition of bacterial flora was evaluated on 16 s rDNA sequencing technique. In the vast majority of samples, bacteria were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Supplementary Figures S1B–D show the most abundant taxa at the Order, Family, and Genus levels. Among these taxa, Streptococcus and Clostridium are commonly found in gallstone samples and have been associated with acute CHL ( Ploszaj et al, 2021 ; Shigemori et al, 2022 ). Notably, we identified that Staphylococcus aureus as the third most abundant Species in the bile samples ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Supplementary Figures S1B–D show the most abundant taxa at the Order, Family, and Genus levels. Among these taxa, Streptococcus and Clostridium are commonly found in gallstone samples and have been associated with acute CHL ( Ploszaj et al, 2021 ; Shigemori et al, 2022 ). Notably, we identified that Staphylococcus aureus as the third most abundant Species in the bile samples ( Figure 2C ).…”
Section: Resultsmentioning
confidence: 99%